Mother Behavior, Husband And Midwife Supported Related to High Risk Pregnancy at Pauh Community Health Center Padang 2015 - Dien Gusta Anggraini Nursal; Rahmi Kasman (Andalas University, Faculty of Public Health, 2018)
High-risk pregnancy is a pregnancy with more dangerous aftermath to pregnancy/labor than normal pregnancy and labor. At Pauh Health Center work zone, there's an increasing rate of high-risk pregnancy from 19.8% at year 2013 to 21.7% at year 2014. The objective of this research is to find out mother behavior, husband and midwife support to high-risk pregnancy at Pauh Community Health Center Padang, 2015. This study is an analytic research with cross sectional study design done in Pauh Community Health Center work zone from January to August 2015. Research population was all of pregnant women (673) in Pauh  Community Health Center work zone. Sampling technique used was purposive sampling to get 61 women. Data was analyzed using chi-square statistical test. Univariate data analysis showed 66,7% respondents had high-risk pregnancy. Bivariate analysis knowledge (p=0,011), attitude (p=0,000), husband (p=0,000), and midwives  (p=0,024) Concluded that high-risk pregnancy incident rate is still high. There's a correlation between knowledge, attitude, husband/family supports, and midwives roles with high-risk pregnancy at Pauh Health Center work zone. It's suggested to midwives working in Pauh Community Health Center to give more information about high-risk pregnancy.